Electrified release of pure CO 2 from postcapture liquid: A two-stage system lowers the total energy cost - Hyun Seung Jung; Hengzhou Liu; Zeyan Liu; Taehee Kim; Ji-Yoon Song; Guangcan Su; Jaerim Kim; Huajie Ze; Ke Xie; Edward H. Sargent (Proceedings of the National Academy of Sciences, 2026)
Electrified carbon capture and release holds promise in carbon management; but it is constrained by high energy demand. Here, we studied two candidate systems for electrochemical CO 2 release from a direct air capture (DAC) postcapture liquid: The first, a hydrogen loop cell, is electricity-efficient, but its evolved CO 2 is mixed with H 2 , introducing a 3 to 4 GJ/tonCO 2 additional energy separation cost. The second system, a solid-state metal oxide redox couple (proton sponge), avoids the gas separation challenge but is stable only in the bicarbonate and not the highly alkaline regime. These considerations led us to examine a two-stage system: An efficient hydrogen loop would first downshift the pH from 13.5 to 9; and a second metal oxide would be used to release CO 2 from bicarbonate. We report an electrified process that provides the release of a pure CO 2 stream from a post-DAC liquid with a measured total energy of ~4.5 GJ/tonCO 2 : 2.4 GJ from the H 2 looping stage and 2.1 GJ from the MnO 2 -based stage—substantially lower than the >=10 GJ/tonCO 2 required by pH-swing methods such as bipolar membrane electrodialysis. We conclude with a generalized analysis of how staged pH downshifting reduces the overall Nernst voltage penalty and facilitates energy-efficient CO 2 release.